The Relationship Between Self-Disclosure And Achievement Motivation In Generation Z (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to see the relationship between self-disclosure and achievement motivation in Generation Z. The subjects in this study were 1,064 people. This research is a correlational study with the research population of generation Z adolescents. The sample used the incidental sampling technique. Data were collected using measuring instruments in the form of a self-disclosure scale (DeVito, 2015) and a ranking of achievement motivation (McClelland, 1987) which the researcher made himself. The statistical tests using the person product moment. The results show that there is a relationship between self-disclosure and achievement motivation in generation Z.